Pseudotumoral and Multiple Retinal Pigment Epithelium Proliferation in Vogt-Koyanagi-Harada Disease - Juan B. Yepez; Felipe Murati; Michele Petitto; J. Fernando Arevalo (Case Reports in Ophthalmological Medicine)
We report a case of pseudotumoral retinal pigment epithelium (RPE) proliferation in Vogt-Koyanagi-Harada (VKH) disease, in a 50-year-old female who presented with a juxtapapillary and peripheral subretinal hyperpigmented lesions in the left eye and “sunset glow fundus,” hyperpigmented striae, and multiple atrophic chorioretinal spots in the periphery. The darkly pigmented exuberant larger subretinal mass extended to the periphery with associated subretinal fibrosis. This patient demonstrated the entire clinical presentation of VKH disease, which tends to course with a chronic, bilateral, granulomatous panuveitis and exudative retinal detachment associated with poliosis, vitiligo, alopecia, and central nervous system and auditory signs. Our case is unique for the presence of exuberant, pseudotumoral RPE proliferation at the juxtapapillary region and peripheral area. Although this complication has rarely been reported, a high index of suspicion is warranted for early diagnosis and avoids unnecessary treatments of a pseudotumor.